Quality of life of irradiated brain tumor survivors treated with donepezil or placebo: Results of the WFU CCOP research base protocol 91105. Issue 2 (6th July 2017) - Naughton, Michelle J; Case, L Douglas; Peiffer, Ann; Chan, Michael; Stieber, Volker; Moore, Dennis; Falchuk, Steven; Piephoff, James; Edenfield, William; Giguere, Jeffrey; Loghin, Monica; Shaw, Edward G; et al.
Abstract: Background: The health-related quality of life (HRQL) and fatigue of brain cancer survivors treated with donepezil or placebo for cognitive symptoms after radiation therapy were examined. Methods: One hundred ninety-eight patients who completed >30 Gy fractionated whole or partial brain irradiation at least 6 months prior to enrollment were randomized to either placebo or donepezil (5 mg for 6 weeks followed by 10 mg for 18 weeks) in a phase 3 trial. A neurocognitive battery, the Functional Assessment of Cancer Therapy-Brain (FACT-Br) and the Functional Assessment of Chronic Illness Therapy (FACIT)-fatigue, was administered at baseline, 12 weeks, and 24 weeks. Results: At 12 weeks, donepezil resulted in improvements in only emotional functioning ( P = .04), with no significant effects at week 24. Associations by level of baseline cognitive symptoms (above or below the median score of the baseline FACT-Br "additional concerns/brain" subscale), indicated that participants with more baseline symptoms who received donepezil versus placebo, showed improvements in social ( P = .02) and emotional well-being ( P = .038), other concerns/brain ( P = .003) and the FACT-Br total score ( P = .004) at 12 weeks, but not 24 weeks. However, participants with fewer baseline symptoms randomized to donepezil versus placebo reported lower functional well-being at both 12 ( P = .015) and 24 weeks ( P = .009), and greater fatigue ( P = .02) at 24 weeks. Conclusions: The positive impact of donepezil on HRQL was greater in survivors reporting more baseline cognitive symptoms. Donepezil had significantly worse effects on fatigue and functional well-being among participants with fewer baseline symptoms. Future interventions with donepezil should target participants with more baseline cognitive complaints to achieve greater therapeutic impact and lessen potential side effects of treatment.